Rekonstruksi Perlindungan Hukum UMKM Dalam Hubungan Bisnis Dengan Korporasi - Heru Wardoyo (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study aims to examine and analyze the legal protection framework for Micro, Small, and Medium Enterprises (MSMEs) in business relationships with corporations, as well as to formulate an ideal reconstruction of legal protection to ensure fairness and balance between the parties. This research employs a normative legal method with a descriptive-analytical nature. The approaches used include statutory and conceptual approaches. The sources of legal materials consist of primary and secondary legal materials. The collection of legal materials was conducted through library research, while the analysis was carried out qualitatively. The results indicate that legal protection for MSMEs in business relationships with corporations remains partial and has not been specifically formulated within a comprehensive regulatory framework. Existing regulations still rely largely on general contract law norms that presume equality between parties. In practice, such assumptions often do not reflect the actual bargaining positions between MSMEs and corporations. Therefore, the reconstruction of legal protection should be directed toward strengthening the principle of contractual fairness, proportionally limiting the principle of freedom of contract, developing more protective standard contracts, providing accessible dispute resolution mechanisms, and reinforcing the state’s role in regulating and supervising MSME–corporate partnerships. Such reconstruction is expected to foster more equitable and sustainable business relationships for MSMEs.